Assessing Malaysia's Manufactured Exports Competitiveness In The East Asian Region: A Shift-Share And Simulation Approach. - Leow, Ghin Yin (2010)

(untitled)
For most East Asian countries, international trade represents a significant portion of their Gross Domestic Product (GDP). Albeit on a different scope and scale, the importance of international trade is rising over the years. Today, trading nations including Malaysia are facing a highly uncertain and demanding external environment with growing competitive pressures. The objective of this thesis is to study Malaysia's manufactured exports competitiveness from 1980-2006 in the East Asian region. Bagi kebanyakan negara Asia Timur, perdagangan antarabangsa menyumbangkan sebahagian besar daripada Keluaran Dalam Negeri Kasar (KDNK) dan kepentingannya kian meningkat. Pada hari ini, kebanyakan negara berdagang termasuk Malaysia menghadapi arena perdagangan antarabangsa yang sangat tak menentu dan mencabar, dengan tekanan saingan yang semakin meningkat. Lantaran itu, objektif tesis ini adalah untuk mengkaji daya bersaing eksport perkilangan Malaysia di antara tahun 1980 sehingga 2006 di rantau Asia Timur.